Karakteristik Dan Model Pendidikan Islam Bagi Abk Tuna Grahita - Maulida Nurul Hikmah; Hilmi Abdussalam Zaini; Rio Saputra; Candra Kirana (CV. ULIL ALBAB CORP, 2021)
This study aims to analyze the characteristics and models of Islamic education for mentally retarded children. The following research is aresearch with a descriptive type of qualitative method. The results of this study indicate that the Islamic education model for mentally retarded children also requires strategies and methods in the learning process, therefore educators need to understand the characteristics of children with special needs and then obtain models in the teaching process. Education is a right and obligation for every individual. Especially for Muslims, namely Islamic education. Islamic religious education is not only given to normal children, but also to children who have mental or mental disorders, including children with mental retardation. In Islamic education, children with mental retardation need to have a model or strategy in their education or learning. Therefore, it is important for educators to understand the characteristics of children with special disorders such as mentally retarded children with special needs. Islamic education for mentally retarded children is usually carried out using oral methods, modeling, and practice.